2020
DOI: 10.7717/peerj.10482
|View full text |Cite
|
Sign up to set email alerts
|

Identification of histone deacetylase genes in Dendrobium officinale and their expression profiles under phytohormone and abiotic stress treatments

Abstract: The deacetylation of core histones controlled by the action of histone deacetylases (HDACs) plays an important role in the epigenetic regulation of plant gene transcription. However, no systematic analysis of HDAC genes in Dendrobium officinale, a medicinal orchid, has been performed. In the current study, a total of 14 histone deacetylases in D. officinale were identified and characterized using bioinformatics-based methods. These genes were classified into RPD3/HDA1, SIR2, and HD2 subfamilies. Most DoHDAC ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…A similar situation also occurs for SmHDA1-3, and the results showed that they differ only in the terminal motifs. On the other hand, SmHDTs does not contain any motifs, a similar pattern has been observed in Dendrobium officinale SRTs [ 24 ].…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…A similar situation also occurs for SmHDA1-3, and the results showed that they differ only in the terminal motifs. On the other hand, SmHDTs does not contain any motifs, a similar pattern has been observed in Dendrobium officinale SRTs [ 24 ].…”
Section: Resultssupporting
confidence: 62%
“…A similar situation also occurs for SmHDA1-3, and the results showed that they differ only in the terminal motifs. On the other hand, SmHDTs does not contain any motifs, a similar pattern has been observed in Dendrobium officinale SRTs [24]. The color of the inner ring represents the species: green, S. miltiorrhiza; red, S. lycopersicum; black, A. thaliana; brown, O. sativa; blue, Z. mays.…”
Section: Gene Structure and Motif Analysis Of Smhdacssupporting
confidence: 63%
“…[95] Triticulum aestivum Drought stress downregulated 5 HDA genes and upregulated TaHAC2 in drought-resistant BL207 [96] Dendrobium hirsutum Under drought stress, the DoHDA10 and DoHDT4 genes are expressed in the roots, stems, and leaves. [97] Arabidopsis thaliana HDA9 reduces plant drought sensitivity via H3K9ac in 14 genes during water deficit [98] Table 2. Cont.…”
Section: Gossypium Hirsutummentioning
confidence: 99%
“…HDAC genes also displayed different transcriptional level to respond to drought. For example, DoHDA10 and DoHDT4 were highly up-regulated after PEG-mediated drought treatment, while other HDAC genes were not changed [52]. Wei et al studied the roles of six HDACs in response to drought stress in kenaf and found up-regulation of all these HDACs after PEG treatments [74].…”
Section: Hdacsmentioning
confidence: 99%